Desenvolvimento e análise das propriedades de medida de tecnologias para avaliação de postura, marcha e função muscular - George Schayer Sabino (2022)
Introduction: Quantitative measures are relevant for physical therapy practice. Often, they are not simple and accessible, which creates a gap between research and clinical practice. This gap happens due to the study object’s complexity and functionality. The technology used has the potential to change this scenario. For example, smartphone use can assist in the quantitative assessment of posture. In addition, sensored insoles can be used to measure plantar pressure during walking. Finally, 3D printer use (i3D) makes it possible to reduce the manufacturing costs of a series of products, such as a manual dynamometer, and can thus facilitate their clinical use. Objectives: To develop and verify the measurement properties of three technological instruments for measuring posture, vertical ground reaction force, and muscle strength. In addition, the impact in methodological variations of the measurement properties of these instruments was investigated. Methods and Results: Three studies were designed to meet the objective of this thesis. In the first study, validity and reliability of a cell phone application to assess knee posture in the frontal plane were evaluated. Furthermore, a different external marker combinations effect on measurement was analyzed. The second study developed and verified validity concurrent and test-retest reliability of a low-cost sensored insole for assessing the ground reaction force during the stance phase of gait. The obstacles in the insole development process and the strategies adopted to overcome them were presented. The cost and durability of the insole were considered appropriate for clinical use. Finally, the third study investigated the concurrent validity and test-retest reliability of an i3D handheld dynamometer to assess knee muscle strength. In addition, this study investigated the impact of using isolated or averaging multiple measurements on measure properties. Conclusions: The use of the PhysioCode application to measure knee posture is valid and presents excellent levels of intra- and inter-examiner reliability. The absence of external markers did not affect the application's measurement properties. The sensor insole used to obtain the ground reaction force data during gait showed excellent concurrent validity levels with the force platform data and testretest reliability. However, the data from the mid-stance phase should be interpreted with caution. Finally, the i3D manual dynamometer is valid and reliable for measuring knee muscle strength, but the average of two or three measurements is recommended for analysis. It is desired that the instruments presented will be used by professionals in the area to assist in their practice in search of the best patient care.